Methodical support of the structural-functional model of physical self-development of girls - future officers in the process of physical education - Sliusarchuk, Victor (Quality in Sport, 2019)
The conducted research was aimed at developing the content for the implementation into practice of the pedagogical model of forming the readiness of girls - future officers for physical self-development in the process of physical education at the military academy. Adequate research methods were used to achieve this goal, including analysis, synthesis, systematization, generalization, and theoretical modeling. Sources of information were selected from science metric databases Scopus, SPORT Discus, Web of Science, university libraries, using keywords. The study of information from literary sources proved the lack of adequate methodical support for the model designed by us for the formation of readiness of girls - future officers for physical self-development in the process of physical education in the military academy. In this regard, appropriate methodological support was developed, the basis of which was the following principles: preliminary design of the educational process and its subsequent reproduction in practice; diagnostic goal setting; structural and content integrity of the pedagogical process; the presence of the content of this process and apprenticeship with initial parameters; the determined direction of the process as totality of diagnostic expediency; objectivity of control over its results. The methodological support developed for the designed model takes into account innovative approaches, modern progressive ideas and the provisions of educational technologies, but requires experimental verification of its effectiveness in achieving the planned result.